Reflections on The concept of law - Simpson, A. W. B. (Alfred William Brian) (Oxford : Oxford University Press, 2011)
H.L.A. Hart developed 'The Concept of Law' while A.W.B. Simpson was studying and teaching at Oxford. Simpson wittily recreates the culture of Oxford philosophy in the '50s, providing a new perspective of one of the most famous works of philosophy of the 20th century and casting a satirical eye over the shortcomings of post-war Oxford.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jurisprudence; Law -- Philosophy; Hart, H. L. A. -- 1907-1992.